Atrial fibrillation prevention: an appraisal of current evidence - Boriani, Giuseppe; Proietti, Marco (Heart (British Cardiac Society), 2018)
Atrial fibrillation (AF), which is the most diagnosed arrhythmia, is becoming a significant issue for health policy-makers. In particular, more and more attention is being devoted to AF prevention. Indeed, several studies recently published point out how targeted interventions could be useful in reducing the risk of AF occurrence (or recurrence). In this review, we briefly summarised the role of the major risk factors associated with the incidence of AF, as well as the effectiveness of interventions aimed at controlling these risk factors. Several general risk factors, such as alcohol consumption, physical activity, smoking habit, as well as specific cardiovascular risk factors as diabetes mellitus, hypertension and obesity have a relevant impact in determining the occurrence of AF, along with a strong clinical evidence of a dose–effect response mechanism for most of the factors examined. Specific interventions aimed at controlling risk factors have been showed to clearly reduce the risk of AF in several cohorts. Even more importantly, integrated programmes aimed at controlling for multiple risk factors would be more efficient in terms of reducing risk of AF, in particular whena stricter control is observed. AF prevention requires a series of initiatives focused on the many risk factors that we reviewed, as well as a more integrated approach, which should involve many stakeholders at different levels. In this light and also considering the constantly changing epidemiology, AF prevention may constitute a future ‘win–win’ strategy for all the stakeholders.